2013
DOI: 10.5194/hess-17-3827-2013
|View full text |Cite
|
Sign up to set email alerts
|

Subsurface release and transport of dissolved carbon in a discontinuous permafrost region

Abstract: Abstract. Subsurface hydrological flow pathways and advection rates through the landscape affect the quantity and timing of hydrological transport of dissolved carbon. This study investigates hydrological carbon transport through the subsurface to streams and how it is affected by the distribution of subsurface hydrological pathways and travel times through the landscape. We develop a consistent mechanistic, pathway-and travel time-based modeling approach for release and transport of dissolved organic carbon (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 59 publications
1
22
0
Order By: Relevance
“…Furthermore, when considering the long-term annual DOC and DIC loads, Jantze et al (2013) reported no significant trends in the total annual mass flux of either DIC or DOC over the periods considered but a significant decreasing trend in total annual discharge for stream 6. Together, this decreasing trend in discharge and increasing trend in DIC concentration can be shown to be consistent with increasing water travel times through the landscape using a mechanistic modeling approach like that outlined in Lyon et al (2010a) and Jantze et al (2013). There are no direct observations of active layer changes from upland soils in the area but it seems likely that these also are affected similar to the observations from the permafrost mires (e.g., Callaghan et al, 2010).…”
Section: The Role Of Shifting Flow Pathways For Dic and Doc Concentramentioning
confidence: 99%
See 4 more Smart Citations
“…Furthermore, when considering the long-term annual DOC and DIC loads, Jantze et al (2013) reported no significant trends in the total annual mass flux of either DIC or DOC over the periods considered but a significant decreasing trend in total annual discharge for stream 6. Together, this decreasing trend in discharge and increasing trend in DIC concentration can be shown to be consistent with increasing water travel times through the landscape using a mechanistic modeling approach like that outlined in Lyon et al (2010a) and Jantze et al (2013). There are no direct observations of active layer changes from upland soils in the area but it seems likely that these also are affected similar to the observations from the permafrost mires (e.g., Callaghan et al, 2010).…”
Section: The Role Of Shifting Flow Pathways For Dic and Doc Concentramentioning
confidence: 99%
“…There are a number of arguments favoring that the observed changes are related to changes in water flow pathways such as those seen in time from the long-term monitoring. For instance, recession flow analysis based on long-term flow records from stream 6 suggests that there has been an increase in the effective aquifer depth in the catchment that could be related to permafrost thaw (Lyon et al, 2009), while analyses of the annual discharges matching the period considered here show decreases in annual total discharge (Jantze et al, 2013). Furthermore, when considering the long-term annual DOC and DIC loads, Jantze et al (2013) reported no significant trends in the total annual mass flux of either DIC or DOC over the periods considered but a significant decreasing trend in total annual discharge for stream 6.…”
Section: The Role Of Shifting Flow Pathways For Dic and Doc Concentramentioning
confidence: 99%
See 3 more Smart Citations